Representation and analysis of soccer players' actions using principal components - Barros, R. M. L.; Cunha, S. A.; Magalhaes, W. J.; Guimaraes, M. F. (Journal of Human Movement Studies, 2006)
This paper proposes the useof the Principal Components Analysis (PCA) method to represent and to analyse soccer players' actions distribution in the pitch.